INTEGRASI DATA PREFERENSI PEMBELAJARAN DAN PLATFORM DIGITAL YANG DIGUNAKAN OLEH MAHASISWA UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN ONLINE - Intan Geandra; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Integration of students learning preference data with digital platforms is a strategic step in increasing the effectiveness of online learning. By understanding individual preferences, educational institutions can present more relevant and personalized content. This study aims to explore how such integration can improve student engagement and learning outcomes. However, challenges such as technological infrastructure and digital skills remain barriers. Therefore, a comprehensive strategy is needed to optimize this integration in the context of higher education in Indonesia.